tudies in Biogeography, Conservation, and Systematics of Peperomia (Piperaceae): Deciphering the historical biogeography, exploring Brazilian endemism and conservation, and bringing to light a new threatened Cerrado species - Moura, Clapton Olimpio de (2023)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Botânica, Programa de Pós-Graduação em Botânica, 2022.